Knowledge and attitude of healthcare professionals to frailty screening in primary care: a systematic review protocol - Gurch Randhawa; Ijeoma Okpechi; David Hewson (BMJ Open)
Introduction Frailty is an increasingly common condition in which physiological decline as a result of accumulated deficits renders older people more vulnerable to adverse outcomes. An increasing range of frailty screening programmes have been introduced in primary care to identify frail older people in order to deliver appropriate interventions. However, limited information on the knowledge and attitude of healthcare professionals (HCPs) with respect to frailty screening is known. The aim of this systematic review is to provide evidence on the knowledge and attitude of HCP in terms of frailty screening, and potentially identify barriers and facilitators to frailty screening to improve implementation of frailty screening in primary care.Methods/design A systematic review of qualitative research will be conducted. Databases searched will be MEDLINE, Cumulative Index to Nursing and Allied Health Literature, PsycINFO and Web of Science from January 2001 to August 2019. Methods will be reported based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Population, interest, context and study design methodology was used to develop inclusion and exclusion criteria with HCPs as population, frailty screening as interest and knowledge or attitude of HCPs to frailty screening as context. Studies with a qualitative methodology or a mixed-method design where the qualitative component is analysed separately will also be included. Quality appraisal will be carried out using the Joanna Briggs Institute appraisal tool for qualitative studies. Data will be extracted from each selected study with thematic framework analysis used to synthesise findings.Ethics and dissemination This systematic review does not require ethical approval as primary data will not be collected. The findings will be disseminated at conferences and in a relevant academic journal. This review will assist HCPs and relevant stakeholders to tackle the challenges of frailty screening in primary care.PROSPERO registration number CRD42019159007.